Motor mapping of the hand muscles using peripheral innervation-based navigated transcranial magnetic stimulation to identify functional reorganization of primary motor regions in malignant tumors - Zhang, Haosu; Zhang, Wei; Ohlerth, Ann-Katrin; Schwendner, Maximilian; Schröder, Axel; Meyer, Bernhard; Krieg, Sandro; Ille, Sebastian (Human brain mapping, 2024)
Tumor-related motor reorganization remains unclear. Navigated transcranial magnetic stimulation (nTMS) can investigate plasticity non-invasively. nTMS-induced motor-evoked potentials (MEPs) of different muscles are commonly used to measure the center of gravity (CoG), the location with the highest density of corticospinal neurons in the precentral gyrus. We hypothesized that a peripheral innervation-based MEP analysis could outline the tumor-induced motor reorganization with a higher clinical and oncological relevance. Then, 21 patients harboring tumors inside the left corticospinal tract (CST) or precentral gyrus were enrolled in group one (G1), and 24 patients with tumors outside the left CST or precentral gyrus were enrolled in Group 2 (G2). Median- and ulnar-nerve-based MEP analysis combined with diffusion tensor imaging fiber tracking was used to explore motor function distribution. There was no significant difference in CoGs or size of motor regions and underlying tracts between G1 and G2. However, G1 involved a sparser distribution of motor regions and more motor-positive sites in the supramarginal gyrus—tumors inside motor areas induced motor reorganization. We propose an “anchor-and-ship theory” hypothesis for this process of motor reorganization: motor CoGs are stably located in the cortical projection area of the CST, like a seated anchor, as the core area for motor output. Primary motor regions can relocate to nearby gyri via synaptic plasticity and association fibers, like a ship moving around its anchor. This principle can anticipate functional reorganization and be used as a neuro-oncological tool for local therapy, such as radiotherapy or surgery.
Gesehen am 23.07.2024
Erstveröffentlichung: 4. März 2024